2018
DOI: 10.1161/hypertensionaha.117.10054
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Predictors of Change in Vascular Function

Abstract: A rterial stiffness measures predict the onset of hypertension and incident cardiovascular disease (CVD) events. [1][2][3][4][5] Cross-sectional correlates of vascular stiffness include age, sex, weight, blood pressure, height, and metabolic features like fasting glucose and lipid levels. 6 Our previous work demonstrated strong, nonlinear relations between age and aortic stiffness measures, suggesting that aortic stiffness increases over time, particularly after midlife.7 Prior work has shown that age-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Moreover, an association between arterial stiffness and triglycerides was also confirmed in subjects with rheumatoid arthritis, as previously reported 3 . Similar results were also reported in a sample of the general population and in patients with metabolic syndrome 4, 5. The relationship between triglycerides and arterial stiffness may involve local and systemic inflammation, oxidative stress and endothelial dysfunction.…”
supporting
confidence: 87%
“…Moreover, an association between arterial stiffness and triglycerides was also confirmed in subjects with rheumatoid arthritis, as previously reported 3 . Similar results were also reported in a sample of the general population and in patients with metabolic syndrome 4, 5. The relationship between triglycerides and arterial stiffness may involve local and systemic inflammation, oxidative stress and endothelial dysfunction.…”
supporting
confidence: 87%
“…Furthermore, a 1-unit increase in the American Heart Association's Life's Simple 7 was associated with 1.55-fold odds for the presence of HVA. The components of Life's Simple 7 most closely associated with HVA were obesity and diabetes, which are also associated with longitudinal change in aortic stiffness (103), suggesting that relatively straightforward lifestyle interventions may prevent stiffening (53), promote HVA, and reduce CVD risk.…”
Section: Excessive Aortic Stiffness and Major Cvd Eventsmentioning
confidence: 99%
“…Longitudinal studies on PWV progression in adults and the elderly have been reported [1926]. The majority of these studies measured PWV at baseline and one follow-up, which does not provide a sufficient basis for studying PWV development with age.…”
Section: Introductionmentioning
confidence: 99%